Comparative phylogeography in the genomic age: Opportunities and challenges. (5th October 2022) - McGaughran, Angela; Liggins, Libby; Marske, Katharine A.; Dawson, Michael N; Schiebelhut, Lauren M.; Lavery, Shane D.; Knowles, L. Lacey; Moritz, Craig; Riginos, Cynthia
Abstract: Aim: We consider the opportunities and challenges comparative phylogeography (CP) faces in the genomic age to determine: (1) how we can maximise the potential of big CP analyses to advance biogeographic and macroevolutionary theory; and (2) what we can, and will struggle, to achieve using CP approaches in this era of genomics. Location: World‐wide. Taxon: All. Methods: We review the literature to discuss the future of CP ‐ particularly examining CP insights enabled by genomics that may not be possible for single species and/or few molecular markers. We focus on how geography and species' natural histories interact to yield congruent and incongruent patterns of neutral and adaptive processes in the context of both historical and recent rapid evolution. We also consider how CP genomic data are being stored, accessed, and shared. Results: With the widespread availability of genomic data, the shift from a single‐ to a multi‐locus perspective is resulting in detailed historical inferences and an improved statistical rigour in phylogeography. However, the time and effort required for collecting co‐distributed species and accruing species‐specific ecological knowledge continue to be limiting factors. Bioinformatic skills and user‐friendly analytical tools, alongside the computational infrastructure required for big data, can also be limiting. Main conclusions: Over the last 35 years, there has been much progress in understanding how intraspecific genetic variation is geographically distributed. The next major steps in CP will be to incorporate evolutionary processes and community perspectives to account for patterns and responses among co‐distributed species and across temporal scales, including those related to anthropogenic change. However, the full potential of CP will only be realised if we employ robust study designs within a sound comparative framework. We advocate that phylogeographers adopt such consistent approaches to enhance future comparisons to present‐day findings.